PRICING POWERED \(α\)-POWER QUANTO OPTIONS WITH AND WITHOUT POISSON JUMPS - Javed Hussain; Nisar Ali (Ural Mathematical Journal)
This paper deals with the problem of Black-Scholes pricing for the Quanto option pricing with power type powered and powered payoff underlying foreign currency is driven by Brownian motion and Poisson jumps, via risk-neutral probability measure. Our approach in this work is probabilistic, based on Feynman–Kac formula.